Financial Performance Analysis of Abdoel Wahab Sjahranie Regional General Hospital, Samarinda: : A Comparative Study Before and After the COVID-19 Pandemic - Irma Rosita; Rita Yuniarti; Prisilia Damayanti (Manunggal Halim Jaya, 2026)
The COVID-19 pandemic, which emerged in December 2019, had a widespread impact on public health and the hospital sector, including RSUD Abdoel Wahab Sjahranie. The surge in patients and the postponement of elective procedures caused financial pressure and revenue fluctuations. Hospital financial management needs to be systematic, accountable, and utilize the latest BLUD financial ratios to comprehensively assess efficiency, liquidity, and profitability. This study aimed to analyze the financial performance of RSUD Abdoel Wahab Sjahranie Samarinda before the COVID-19 pandemic during 2018–2020, after the COVID-19 pandemic during 2021–2023, and the differences in financial performance before and after the pandemic. This study employed a descriptive comparative mixed methods design, with the population consisting of all RSUD Abdoel Wahab Sjahranie financial reports from 2018–2023. Key informants consisted of three individuals: the Deputy Director of General Affairs and Finance, the Head of the Finance Division, and the Head of the Accounting Division of RSUD Abdoel Wahab Sjahranie Samarinda. A purposive sample of six annual financial reports was used. Instruments included interview guidelines and financial reports. Quantitative data were analyzed using financial ratios based on the Regulation of the Director General of Treasury Number PER-24/PB/2018. The study results showed that the financial performance of RSUD AWS before the pandemic showed declines in liquidity, asset effectiveness, and profitability, resulting in a total score of 27.25, categorized as Poor (CC). After the pandemic, cash liquidity continued to decline, the collecting period fluctuated, and profitability remained negative, although the current ratio improved; the total score of 27.5 was still categorized as Poor (CC). There was a difference in financial performance of RSUD Abdoel Wahab Sjahranie Samarinda between the periods before and after the COVID-19 pandemic.